2011
DOI: 10.1074/jbc.m111.228981
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of p53 DNA Binding Function by the MDM2 Protein Acidic Domain

Abstract: MDM2 regulates p53 predominantly by promoting p53 ubiquitination. However, ubiquitination-independent mechanisms of MDM2 have also been implicated. Here we show that MDM2 inhibits p53 DNA binding activity in vitro and in vivo. MDM2 binding promotes p53 to adopt a mutant-like conformation, losing reactivity to antibody Pab1620, while exposing the Pab240 epitope. The acidic domain of MDM2 is required to induce p53 conformational change and inhibit p53 DNA binding. Alternate reading frame binding to the MDM2 acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 63 publications
2
57
0
Order By: Relevance
“…Phosphorylation of the acidic domain by GSK3 stimulates ubiquitination of p53 (22,23). We showed that the acidic domain also causes conformational changes in the p53 core and that the MDM2-p53 complex does not bind DNA (10). The MDM2 acidic domain-p53 core interaction may serve to position the C-terminal RING for efficient ubiquitination of p53 C-terminal lysines or expose the target lysines in the p53 core domain.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Phosphorylation of the acidic domain by GSK3 stimulates ubiquitination of p53 (22,23). We showed that the acidic domain also causes conformational changes in the p53 core and that the MDM2-p53 complex does not bind DNA (10). The MDM2 acidic domain-p53 core interaction may serve to position the C-terminal RING for efficient ubiquitination of p53 C-terminal lysines or expose the target lysines in the p53 core domain.…”
Section: Discussionmentioning
confidence: 92%
“…Our results showed that the structural integrity of this region is critical for p53 ubiquitination. We recently also showed that ARF inhibits the ability of MDM2 acidic domain to induce p53 misfolding (10). Therefore, ATM phosphorylation of MDM2 and ARF binding appear to exert similar effects on the acidic domain function (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(27)(28)(29), the deubiquitinating enzyme HAUSP (30), ribosomal proteins (19), and the tumor suppressor ARF (31). Furthermore, the MDM2 acidic domain can bind weakly to the p53 core domain and induces p53 conformational change (32)(33)(34)(35)(36). The flexibility of the acidic domain is probably critical for interactions with multiple protein partners (37,38).…”
mentioning
confidence: 99%
“…Recent results show that bortezomib induces the binding of p53 on DNA, promotes transcription factors and inhibits MDM2 [15].…”
Section: Inhibition Of P53mentioning
confidence: 99%